The WEB-BASED EMPLOYEE LEAVE APPLICATION INFORMATION SYSTEM USING THE WATERFALL METHOD - Cahayati Annisa Qawakib; Jamaludin Jamaludin (Institute of Computer Science (IOCS), 2022)
Information systems are the most important part in running and managing a data source. One of them is a website -based employee leave application information system . The website -based employee leave application information system at the Medan City Central Statistics Agency still uses the manual method written in an employee leave application form. The system development method in this study, the author uses the waterfall method where the collection techniques are in the form of observation and interviews. In the implementation and design of the program the author uses the PHP programming language with the database used is My SQL to store data. The results of this study can be concluded that with the creation of a website -based employee leave application information system, it is expected to simplify and speed up the employee leave application process so that it can reduce errors in processing employee leave applications.